1997
DOI: 10.1097/00005537-199712000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Gold Weight Eyelid Implants for Treatment of Fifth and Seventh Nerve Paralysis

Abstract: Complications occurred in six patients after gold weights were implanted into the upper eyelid tissues for fifth and seventh nerve palsies. These complications included implant infection without extrusion (in one patient); entropion with trichiasis and presumed inflammatory reaction to the gold weight material (in one patient); upper eyelid distortion and poor eyelid contour with corneal ulceration and scarring (in one patient); significant residual lagophthalmos with exposure keratitis (in one patient); and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 11 publications
0
21
0
2
Order By: Relevance
“…We have described one patient who experienced this reaction at our centre. Our literature search revealed only three articles that describe this complication, and they report on a total of six patients (5,8,9). Although a rare complication, when it occurs, the outcomes tend to be poor, because most patients will require removal of their implant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have described one patient who experienced this reaction at our centre. Our literature search revealed only three articles that describe this complication, and they report on a total of six patients (5,8,9). Although a rare complication, when it occurs, the outcomes tend to be poor, because most patients will require removal of their implant.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of this reaction, however, is not certain. Previous studies have examined tissue samples taken from patients who had their gold weights removed (5,8,9). Based on pathological specimens, Doyle et al (8) suggested that this complication is mediated by a type IV hypersensitivity reaction to gold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesos de platina podem ser usados em pacientes com alergia ao ouro 3 . A melhora da PF é multifatorial, mas primordialmente influenciada pela causa da paralisia, grau de lesão neural, local da lesão, idade e condições clínicas do paciente.…”
Section: Discussionunclassified
“…Complicações mais raras como diplopia monocular, astigmatismo e lagoftalmo residual também são descritos 3 . A taxa de extrusão do peso variou na literatura de 0% (8) a 10% 10 .…”
Section: Discussionunclassified